THE INFLUENCE OF INDIVIDUAL CHARACTERISTICS, WORKLOAD, AND WORK ENVIRONMENT ON THE PERFORMANCE OF EMPLOYEES IN PT XYZ'S SUPPLY CHAIN MANAGEMENT AND TECHNICAL PLANNING DIVISION - Siti Serafina; Kholil Kholil; Derinta Entas (SEAN Institute, 2023)
This research aims to determine the extent to which the influence of individual characteristics, workload, and work environment affect employee performance. By conducting this research, it is expected to assist the company in identifying the appropriate strategies to enhance employee performance. The research results indicate a significant influence of the variables of individual characteristics, workload, work environment, and employee performance in PT XYZ company, with T-Statistic values > 1.96 and P-Values < 0.05.